Violência infantil e o seu contexto: experiências vivenciadas em escolas de educação básica - Teruel, Gabriela Peres [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Brito, Carla Perri de [UNESP]; Albulquerque, Ana Laura Modesto [UNESP]; Dias, Isabella Andrade [UNESP]; Garbin, Artênio José Isper [UNESP]; Arcieri, Renato Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The violence against children can be noticed in everywhere, and it is a huge challenge to the authorities nowadays, making the population aware about the importance of notifying authorities about it. Violence against children is increasing, including in the confines of their families. This search aims to report the experience of the project “Violence Identification against children in Primary Public Schools” the undergraduate students of FOAUNESP develop skills to detect, notify, and conduct the violence cases founded, it also awares all the people involved in children’s day a day about the cases of violence. This project is developed in the city of Araçatuba for 7 years, attending approximately 1,000 children 0-6 years in 10 schools every year. During those years the project reports an increase prevalence of abuses and negligence from parents and relatives about children care. The verified cases has been described in resources, identifying the location and the form of the violence, and all the child abuses were reported to school staff and to the Guardian Council. Other educational programs are also developed to teaching staff, parents and relatives to change their behavior in the family ambit. By this way, the activities to fight against the violence in childhood developed by FOA – UNESP can reach an integration of the university and community, changing the real concepts of the population about it, and in addition, helping on identifying the violence and protecting children against it.

A violência contra o menor pode ser observada em todo o mundo, sendo que o grande desafio das autoridades nos dias atuais permeia a conscientização da população a respeito da importância da notificação. Os abusos contra a criança são crescentes e muitos ocorrem em âmbito familiar. Dentro deste contexto, este trabalho busca relatar a experiência do projeto de extensão “Identificação de violência contra crianças nas Escolas Municipais de Ensino Básico (EMEBs) de Araçatuba-SP” os alunos de graduação da FOAUNESP desenvolvem habilidades de detecção, notificação e condução de casos de violência encontrados, bem como sensibilização de todos os atores sociais envolvidos no cotidiano do pré- escolar a respeito de violência. Este projeto é desenvolvido no município de Araçatuba há 7 anos, atendendo, aproximadamente, 1000 crianças de 0 a 6 anos, em 10 escolas por ano. Foi possível observar ao longo desses anos de realização do projeto que existe uma prevalência maior de abusos relacionados à negligência dos pais ou responsáveis no cuidado dos menores. Os casos verificados foram descritos em fichas, ressaltando a identificação do local e do tipo de agressão, sendo que todos os abusos foram informados à direção da escola e posteriormente encaminhados ao Conselho Tutelar. Também são desenvolvidos programas de educação aos professores e aos pais para que haja uma mudança de comportamento no núcleo familiar. Sendo assim, as atividades no combate aos maus-tratos na infância pela FOAUNESP, conseguem maior interação da universidade com a comunidade, transformando os reais anseios da população, além de auxiliar na identificação de abusos e na proteção das crianças contra a violência.
Keywords: Violence; Children; Public health; Violência; Criança; Saúde pública